E-government concept and e-government applications in Turkey - Sisman, Aziz; Sesli, F. Ahmet; Alkis, Zuebeyde (ACADEMIC JOURNALS, 2009)
Government and private organizations all around the world and Turkey have attempted to new searches and investments for making their services rapid, independent from space/time, comfortable and contemporary and also increasing their services' quality by employing the opportunities offered by the internet technology. By the electronic government (e-government) concept developed as a result of these efforts, the opportunity that the citizen and the government can execute their mutual duties and obligations via electronic communication and process media has appeared. The main target of e-government is to create a government structure, which its data process capacity is increased and can make decisions and satisfy the requirements immediately. In this study, e-government necessity for Turkey and which factors affect negatively e-government formation were studied and also Turkey's main government organizations' projects and applications on e-government were defined by determining the position occupied by Turkey, which it is economy is still developing, on the world.
Keywords: E-government; internet; e-readiness; Business & Economics